Preparation and thermal properties of bio‐based gallic acid epoxy/carbon nanotubes composites by cationic ring‐opening reaction. Issue 10 (22nd April 2015) - Hou, Guixiang; Li, Na; Han, Hongzhe; Run, Mingtao; Gao, Jungang
Abstract : In order to prepare the bio‐based polymeric materials, a gallic acid epoxy resin (GA‐ER) is synthesized by using biodegradable gallic acid, and the nanocomposites of GA‐ER/glycidyl methacrylate (GMA)/multiwalled carbon nanotubes (MWCNTs) were prepared by dual hybrid cationic ring‐opening reaction. Differential scanning calorimetry (DSC) results show that the curing reaction temperature of the nanocomposites is between 150 and 225°C. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) results suggest that MWCNTs are homodispersing in the GA‐ER/GMA matrix when the MWCNTs content is not more than 1.0 wt%. The glass transition temperature of the nanocomposite with 0.5 wt% MWCNTs is 9.3°C higher than that of pure resin system. The initial thermal degradation temperature and degradation activation energies E a of the nanocomposite with 1.0 wt% MWCNTs is 10°C and 68.6 kJ/mol higher than that the pure resin system, respectively. POLYM. COMPOS., 37:3093–3102, 2016. © 2015 Society of Plastics Engineers